High prevalence of ALPK3 premature terminating variants in Korean hypertrophic cardiomyopathy patients - Ryu, Seung Woo; Jeong, Won Chan; Hong, Geu Ru; Cho, Jung Sun; Lee, Soo Yong; Kim, Hyungseop; Jang, Jeong Yoon; Lee, Sun Hwa; Bae, Dae-Hwan; Cho, Jae Yeong; Kim, Ji Hee; Kim, Kyung-Hee; et al. (Frontiers in Cardiovascular Medicine, 2024)
The alpha-protein kinase 3 (ALPK3) gene (OMIM: 617608) is associated with autosomal recessive familial hypertrophic cardiomyopathy-27 (CMH27, OMIM: 618052) that presents with severe early-onset hypertrophic or dilated cardiomyopathy with biventricular involvement and atypical distribution of hypertrophy. Recently, several studies have shown that monoallelic premature terminating variants (PTVs) in ALPK3 are associated with adult-onset autosomal dominant hypertrophic cardiomyopathy (HCMP). However, these studies were performed on patient cohorts mainly from European Caucasian backgrounds. To see if this finding is replicated in the Korean HCMP cohort, we evaluated 2,366 Korean patients with non-syndromic HCMP. When compared to three independent population databases, we observed that monoallelic PTVs in ALPK3 were also significantly enriched in Korean HCMP patients with an odds ratio score of 10~21. Therefore, we suggest that ALPK3 PTV carriers be considered a risk group for developing HCMP and monitored for cardiomyopathies.